2001
DOI: 10.1524/ract.2001.89.8.499
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aerobic soil bacteria with plutonium(VI)

Abstract: Plutonium / Bacillus sphaericus / Pseudomonas stutzeri / Biosorption / Absorption spectroscopy / ActinidesSummary. We studied the interaction of Pu(VI) with Pseudomonas stutzeri ATCC 17588 and Bacillus sphaericus ATCC 14577, representatives of the main aerobic groups of soil bacteria present in the upper soil layers. The biosorption studies have shown that these soil bacteria accumulate high amounts of Pu(VI). The relative sorption efficiency toward Pu(VI) related to the amount of biomass used decreased with i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(55 citation statements)
references
References 15 publications
2
53
0
Order By: Relevance
“…Microorganisms are associated with a variety of radioactive materials at U.S. Department of Energy contaminated sites (14,15), and it is apparent that Pu speciation and solubility can be affected by microbial activity (16)(17)(18)(19)(20)(21). Previous studies of Pseudomonas stutzeri and Bacillus sphaericus reported a sorption affinity of nearly 100 g Pu/g dry cell weight for Pu(VI) to the surface of vegetative cells and spores (20).…”
Section: Importancementioning
confidence: 99%
See 1 more Smart Citation
“…Microorganisms are associated with a variety of radioactive materials at U.S. Department of Energy contaminated sites (14,15), and it is apparent that Pu speciation and solubility can be affected by microbial activity (16)(17)(18)(19)(20)(21). Previous studies of Pseudomonas stutzeri and Bacillus sphaericus reported a sorption affinity of nearly 100 g Pu/g dry cell weight for Pu(VI) to the surface of vegetative cells and spores (20).…”
Section: Importancementioning
confidence: 99%
“…Previous studies of Pseudomonas stutzeri and Bacillus sphaericus reported a sorption affinity of nearly 100 g Pu/g dry cell weight for Pu(VI) to the surface of vegetative cells and spores (20). Further investigations of Pu on B. sphaericus by extended X-ray absorption fine-structure (EXAFS) spectroscopy revealed that an insoluble Pu(VI) phosphate complex can form on the cell surface (22).…”
Section: Importancementioning
confidence: 99%
“…These siderophores ensure the availability of essential metals, such as cobalt, copper, iron, and nickel (63,64,224,313,345). Furthermore, several P. stutzeri strains have been described due to their high biosorption potential and resistance to metals such as aluminum (422), chromium (12,172), cobalt (172), copper (69,215), germanium (370), lead (215), manganese (172), nickel (272,346), plutonium (255), selenium (157), silver (135), thallium (172), titanium (38), uranium (172), vanadium (172), and zinc (34,172,215).…”
Section: Biodegradation and Useful Properties For Biotechnological Apmentioning
confidence: 99%
“…In addition, the interaction with the bacteria can cause changes in the oxidation state of plutonium under environmental conditions [17,18]. The published material provides much useful information on the mobility of plutonium, but some of these publications are contradictory, especially regarding the oxidation state and speciation of plutonium at low pH values, and also the data obtained from the experiments conducted without the determination of the oxidation state of plutonium.…”
Section: Introductionmentioning
confidence: 99%